AB0239 EFFECTS OF DYSMETABOLISMS AND COMORBIDITIES ON THE EFFICACY, SAFETY AND RETENTION RATE OF BIOLOGICAL DMARDS (bDMARD) IN INFLAMMATORY JOINT DISEASES. (2nd June 2020) - Cometi, L.; Bruni, C.; Chiti, N.; Tofani, L.; Nacci, F.; Bartoli, F.; Bellando Randone, S.; Fiori, G.; Guiducci, S.; Matucci-Cerinic, M.
Abstract : Background: bDMARDs have an effect on glucose homeostasis (1), lipoproteins profile (2; 3) and blood pressure (4). However, with the exception of obesity (5; 6), there are no clear data on how bDMARDs work in patients who already have or develop metabolic comorbidities and whether these conditions can impact on their efficacy and safety profile. Objectives: to evaluate, in chronic inflammatory joint diseases, the effect of arterial hypertension (AH), dyslipidemia (DYS) and diabetes mellitus (DM) on efficacy, safety and retention rate of first-line bDMARDs therapy. Methods: a retrospective observational study on the clinical charts of Rheumatoid Arthritis (RA), Psoriatic Arthritis (PsA) or Ankylosing Spondylitis (AS), treated with first on-label bDMARD was performed. Data on adverse events, efficacy and comorbidities at the baseline visit in which the bDMARD was prescribed (BL), the visit performed after 6 months of therapy (6M), and the last visit on treatment (LoT) were collected. Results: 383 patients (41, 8% RA, 33, 4% PsA and 24, 8% AS) were included in the study, with the predominance of females (F: 67, 36%, M: 32, 64%; mean age 51, 67 ± 15, 11 years). Our data show that the presence of comorbidities had no influence on efficacy of bDMARD, while patients who had DYS at BL manifested a higher rate of systemic adverse events either in the first 6 months of therapy (58, 9% vs 43, 7%, p=0, 040) and also later on (80, 36% vs. 66, 67%, p=0, 046). In addition, patients who developed DYS and AH after the 6M visit reported a higher rate of systemic adverse events at LoT visit, compared to others (DYS: 97, 8% vs 66, 7%, p<0, 001; AH: 86, 9% vs 65, 2%, p=0, 031). For what concerns the retention rate, patients who developed DYS or AH during bDMARD treatment continued the drug for a longer period of time (DYS 95, 5 vs 19, 6 months, p<0, 001; AH 72, 1 vs 23, 4 months, p<0, 001). In particular, patients with AH who concomitantly carried out therapy with ACE-inhibitors (ACEi) and/or angiotensin II receptor blockers (ARB) continued bDMARDs for nearly 20 more months than patients who were not exposed to these drugs (40, 5 vs 23, 4 months, p=0, 001) and more frequently maintained the bDMARDS at LoT (59, 42% vs. 47, 53%). In case of withdrawal in the ACEi/ARB exposed cohort, this was due to well-being and disease remission rather than inefficacy or adverse reaction (p=0, 025). In dyslipidemic patients treated with statins, data showed that bDMARDs were continued for a longer time than in DYS patients treated with other anti dyslipidemic therapies (41, 09 vs. 26, 50 months, p=0, 042). Conclusion: our data suggest that AH and DYS may be associated with higher frequency of adverse events but a better drug retention. The combination of bDMARD and ACEi/ARB may determine a better control of the inflammatory process by inhibition of angiotensin II, favouring the achievement of remission. In AH patients on bDMARDs, ACEi and ARB could therefore represent an useful anti-hypertensive drug choice. Similarly, statins could be the treatment of choice in DYS patients. References: [1]Gonzalez-Gay MA, et al. Clin Exp Rheumatol. 2006. [2]Pollono EN, et al. Clin Rheumatol. 2010 [3]van Sijl AM, et al. Semin Arthritis Rheum. 2011. [4]Yoshida S, et al. J Hum Hypertens. 2014. [5]Gremese E, et al. Arthritis Care Res (Hoboken). 2013. [6]Heimans L, et al. Arthritis Care Res (Hoboken). 2013. Disclosure of Interests: Laura Cometi: None declared, Cosimo Bruni Speakers bureau: Actelion, Eli Lilly, Nicolò Chiti: None declared, Lorenzo Tofani: None declared, Francesca Nacci: None declared, Francesca Bartoli: None declared, Silvia Bellando Randone: None declared, Ginevra Fiori: None declared, Serena Guiducci: None declared, Marco Matucci-Cerinic Grant/research support from: Actelion, MSD, Bristol-Myers Squibb, Speakers bureau: Acetelion, Lilly, Boehringer Ingelheim